Upaya Menambah Daya Tarik Objek Wisata Melalui Rancangan Spot Foto Pantai Pasetran Gondo Mayit Blitar - Arif Zunaidi; Misbahul Munir; Abdul Qodir Zailani; Nur Muhammad; Darmansyah Darmansyah; M. Miftahul fanani; Fahimatul Ilmiyah; Nisaul Karimah; Rahma Indika; Nabilla Ayu Febrianti (LPPM Universitas Trunojoyo Madura, 2022)
A tourist attraction is one of the main assets that must be owned in an effort to increase and develop a tourist attraction. In order to increase tourist visits to the Pasteran Gondo Mayit beach tourism object, the KKN 108 IAIN Kediri team took the initiative to cooperate with the village government to add photo spots at the tourist attraction location. It is hoped that the existence of this photo spot will increase tourist visits, which in turn will have an impact on increasing regional income obtained from entrance tickets and parking. In addition, the increase in visitors will also have an impact on increasing the income of traders from Tambakrejo village. The method used in this service activity is called PAR (Participatory Action Research), which looks at the needs of the service location and also community participation. Overall, this activity has been successfully carried out by inviting villagers to participate in making photo spots to increase the attractiveness of tourist objects.